Communication media types for optimising yards in achieving family food security - Selly Oktarina; Eko Purwanto; Abdul Basit; Mirza Shahreza (Faculty of Communications Science, Dr. Soetomo University, 2023)
Food security, particularly at the family level, is closely linked to women farmers' effective utilisation of yards. This study emphasises the significance of communication media as valuable sources of information for optimising yard spaces. Various forms of communication media, including forums, electronic, digital, and print media, play a crucial role in this context. The research employs a quantitative approach with qualitative data, adhering to a post-positivistic paradigm. Cluster sampling was used, involving 103 women farmers as the sample group. Quantitative data processing and analysis were performed using the scoring and descriptive methods. The findings reveal that direct communication methods, such as consulting neighbours, family members, fellow farmers within women's groups, and external contacts, are preferred by women farmers. Indirect communication via forums like WhatsApp (WA) meetings also serves as an essential platform for discussions, information exchange, and sharing experiences related to yard utilisation.